Efektivitas Kegiatan Kuliah Tujuh Menit (Kultum) Dalam Membentuk Kepercayaan Diri Siswa Kelas V Di SDIT Assalam Garut Kota - Izzan, Ahmad; Oktaviani , Nopi (STAI Al-Musaddadiyah Garut, 2022)
Self-confidence is a crucial element for students to develop their potential effectively. However, issues surrounding students' self-confidence often demand significant attention. Indicators of low self-confidence among students include a lack of self-belief, optimism, objectivity, responsibility, and rational as well as realistic thinking. Consequently, these students struggle to harness their full potential. One viable approach to addressing this issue is through the implementation of the